IMPACT OF TRANSFORMATIONAL LEADERSHIP ON PROJECT SUCCESS CRITERIA: THE MODERATING ROLE OF WORK ENGAGEMENT. - Saeed Muhammad, Temoor Anjum, Fahad Khan Afridi, Dr. Imran Ibrahim Alasan (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The study aims to identifying the impact of transformational leadership on project success criteria by assessing the moderating effect of work engagement. A quantitative study was conducted to test the hypothesis and structured questionnaires used to collected data from respondents. The adapted questionnaires were sent to the stakeholders having an interest in PSDP (Public Sector Development Program) projects in KPK (Khyber Pakhtunkhwa). The sample size was calculated based on relevant stakeholders attached to PSDP construction projects in the higher education sector of KPK. Results illustrate that transformational leadership has a positive and significant impact on project success criteria. Furthermore, employee engagement has also found a positive and significant effect on project success criteria. Moreover, interaction effect found a negative and significant impact on the project success criteria. This study is beneficial for the managers/supervisor of the PSDP projects. This study also has some limitation because of small sample size and cross-sectional study.